2022
DOI: 10.3389/fpubh.2022.924748
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Internet Videos Related to Pediatric Urology in Mainland China: A Cross-Sectional Study

Abstract: BackgroundPediatric urological diseases pose serious threats to children's physical and mental health. The COVID-19 pandemic has resulted in poor pediatric outcomes for cryptorchidism, hypospadias, and testicular torsion. Presently, many people tend to seek health information via social media platforms. This study aims to quantitatively assess the quality of videos as an information source for pediatric urology in mainland China.MethodsIn this cross-sectional study, a search was performed on social media platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
4
13
0
Order By: Relevance
“…Yet videos produced by these two sources did not receive the most “likes,” “comments,” “shares,” or “saves”. This finding indicates that the quality of the videos is not related to popularity, which is consistent with previous research results 24 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Yet videos produced by these two sources did not receive the most “likes,” “comments,” “shares,” or “saves”. This finding indicates that the quality of the videos is not related to popularity, which is consistent with previous research results 24 …”
Section: Discussionsupporting
confidence: 93%
“…This finding indicates that the quality of the videos is not related to popularity, which is consistent with previous research results. 24 Previous studies showed that the quality of health-related videos produced by nonprofit organizations was higher than those produced by other sources, 12,15 which was consistent with our results.…”
Section: Overall Quality Mean (Sd)supporting
confidence: 93%
See 1 more Smart Citation
“…Considering the existing barriers to promoting child and adolescent vision health in families ( 6 ), popular social media apps like TikTok can be easily accessed by parents and young people to receive myopia information. Some previous studies have evaluated adolescent health issues related to TikTok, such as social media addiction ( 26 ), vaping content ( 27 ), mental health/disorder among adolescents ( 28 , 29 ), and pediatric urology ( 30 ). However, TikTok videos on adolescent vision health have been seldom evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…TikTok, iQiyi, Bilibili, and Weibo are the most popular social media platforms in China, each with hundreds of millions of active users. However, although there are studies that have compared and studied the videos of other specialties on some platforms ( 7 9 ), thus far, none exists about thoracic surgery. Therefore, this study chose lung nodules, a hot topic in thoracic surgery, as an entry point to evaluate the quality of videos related to thoracic surgery on these platforms.…”
Section: Introductionmentioning
confidence: 99%